Metode Akidah Golongan Mu‘tadilah Berkenaan Sifat Khabariyyah: Suatu Pengenalan: The Method of Beliefs of The Mu'tadilah Regarding The Nature of Khabariyyah: An Introduction - Nasron Yaacob (RABBANICA - Journal of Revealed Knowledge, 2023)
In understanding the khabariyyah nature of Allah SWT, Muslims among the Ahli Sunnah wal Jamaah have had a difference of opinion in determining the method of belief between the methods of ithbat, ta'wil and tafwid. This dispute has been going on for a long time and has taken a very long time until today. However, there are still several Muslims who still believe in the point of unity through the unification of the ummah between all the conflicting methods. The study of the article here names the group of peacemakers as the mu'tadilah group, which is simple and open to understanding the nature of khabariyyah. This study’s objective is to identify the method of mu'tadilah belief in the issue of the nature of Allah SWT's khabariyyah, which sets the goal of reaching a point of commonality and the unification of faith among Muslims. This study uses a qualitative approach through a content analysis research design, which analyses documentation materials such as articles, books, journals, proceedings and written reports. The results found that the mu'tadilah method is simple among the methods of ithbat, ta'wil and tafwid. Even if a specific figure adheres to a particular faith method, other methods are still considered and accepted as part of the Ahli Sunnah wal Jamaah faith. Therefore, the mu'tadilah belief method is considered the ideal and best method of unifying the ummah. This study is expected to be able to ease the long-standing belief method dispute between the methods of ithbat, ta'wil and tafwid through this simple mu'tadilah thought as advocated by Islam, further realising the unification of the ummah as aspired to. Dalam memahami sifat khabariyyah Allah SWT, umat Islam kalangan Ahli Sunnah wal Jamaah telah berselisih pandangan dalam menentukan metode akidahnya antara metode ithbat, ta’wil dan tafwid. Perselisihan ini telah berlangsung sekian lama dan memakan masa yang sangat panjang sehingga ke hari ini. Namun begitu masih ada sebilangan umat Islam yang tetap percaya pada titik kesatuan melalui wadah penyatuan ummah antara semua metode yang berselisih tersebut. Kajian ini menamakan kumpulan pendamai itu sebagai golongan mu‘tadilah, yang bersifat sederhana dan terbuka dalam memahami sifat khabariyyah. Objektif kajian ialah mengenal pasti metode akidah mu‘tadilah dalam isu sifat khabariyyah Allah SWT bagi mencapai titik persamaan dan penyatuan akidah dalam kalangan umat Islam. Kajian ini menggunakan pendekatan kualitatif melalui reka bentuk kajian analisis kandungan, iaitu analisis terhadap bahan dokumentasi seperti artikel, buku, jurnal, prosiding dan laporan bertulis. Hasil kajian mendapati bahawa metode mu‘tadilah ialah metode yang sederhana di antara metode ithbat, ta’wil dan tafwid. Walaupun seseorang tokoh itu berpegang dengan metode akidah pilihannya yang tertentu, namun metode akidah lain juga masih diterima sebagai sebahagian daripada akidah Ahli Sunnah wal Jamaah. Justeru metode akidah mu‘tadilah ini dilihat sebagai metode penyatuan ummah yang ideal dan terbaik. Kajian ini diharap dapat meredakan pertikaian metode akidah yang sekian lama berlanjutan antara metode ithbat, ta’wil dan tafwid melalui pemikiran mu‘tadilah yang sederhana ini seperti yang dianjurkan oleh Islam, seterusnya merealisasikan usaha penyatuan ummah sebagaimana yang dicita-citakan.